Relation extraction in vietnamese text using label propagation. - Rathany, Sam Chan; Hương, Lê Thanh; Thủy, Nguyễn Thanh; Long, Nguyễn Thành; Dũng, Trịnh Minh (Journal of Computer Science and Cybernetics, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><span style="font-size: 11.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: TimesNewRoman; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;">This paper presents a relation extraction system for Vietnamese texts using label propagation. In this paper, we propose: (i) a measure of similarities between two sentences; (ii) a method to decrease the effect of high frequency labels in the documents. <span style="font-size: 11.0pt; mso-bidi-font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;">Our experimental results show that proposed label propagation method achieves a higher accuracy than the ordinary one [10]. Moreover, its accuracy is also higher than the support vector machine method applied.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>